Superoxide Anion Disproportionation Induced by Li+ and H+: Pathways to 1O2 Release in Li−O2 Batteries. Issue 18 (20th August 2020) - Pierini, Adriano; Brutti, Sergio; Bodo, Enrico
Abstract: We explore the disproportionation reaction of superoxide anions in the presence of H + and Li + cations with high quality multiconfigurational ab‐initio methods. This reaction is of paramount importance in Li−O2 battery chemistry as it represents the source of a major degrading impurity, singlet molecular oxygen. For the first time, the thermodynamic and kinetic data of the reaction are drawn from an accurate theoretical model where the electronic structure of the reactant and products is treated at the necessary level of theory. Overall, the H + catalyzed O2 − +O2 − disproportionation follows a very efficient thermodynamic and kinetic reaction path leading to neutral 3 O2, 1 O2 and peroxide anions. On the contrary, we have found that the Li + catalysis promotes only the release of 3 O2 whereas the 1 O2 formation is energetically unfeasible at room temperature. Abstract : Accurate calculations show how the main chemical pathway to the detrimental formation of singlet oxygen in Li−O2 electrochemical cells is due to an efficient proton‐catalyzed superoxide disproportionation.